Early Versus Delayed Feeding in Paediatric Patients Following Stoma Reversal in a Resource Limited Environment - Muhammad Javaid Iqbal; Asif Iqbal; Mohammad Sajjad Anwer; Sajid Hameed Dar (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2020)
Introduction: Institution of early enteral nutrition is essential after stoma reversal. There is no consensus on the time feeding should be started after closure of a stoma in children. It is established that after stoma reversal early achievement of full feed and early discharge affects the overall cost in resource limited countries. Materials and Methods: This Randomized control trial was conducted in the Paediatric Surgery Department of Services Hospital, Lahore. Over a period of 1 year, from April 2016 to March 2017, a total of 100 cases were included.  In group A, early feeding (after 36 to 48hours) and in group B delayed (after 5days) feeding was given to the patients. Time for restoration of full feed and length of hospital stay and complications were compared in both groups. Each patient was observed in the ward till discharge and followed up to 30 days in the out-patient department. The data was recorded and analyzed in SPSS version 20. Independent sample t-test was applied to obtain the p-value for comparing the means. P-value ≤ 0.05 was considered significant. Results:  In both groups age, weight and etiology of stoma was comparable.  The full feed was achieved within 56.66 ± 7.77 hours in group A and 156.76 ± 7.96 hours in group B (P<0.005). Mean length of hospital stay was 5.84 ± 0.84 days in group A, while it was 9.50 ± 0.76 days in group B (P<0.005). Conclusion: Early enteral feeding after stoma reversal is well tolerated and beneficial. It is suggested that early feeding protocol should be encouraged in a resource limited environment.